Superconducting spin valve effect in Co/Pb/Co heterostructures with insulating interlayers - Kamashev, Andrey A.; Garif’yanov, Nadir N.; Validov, Aidar A.; Kataev, Vladislav; Osin, Alexander S.; Fominov, Yakov V.; Garifullin, Ilgiz A. (Beilstein Journal of Nanotechnology, 2024)
We report the superconducting properties of Co/Pb/Co heterostructures with thin insulating interlayers. The main specific feature of these structures is the intentional oxidation of both superconductor/ferromagnet (S/F) interfaces. We study the variation of the critical temperature of our systems due to switching between parallel and antiparallel configurations of the magnetizations of the two magnetic layers. Common knowledge suggests that this spin valve effect, which is due to the S/F proximity effect, is most pronounced in the case of perfect metallic contacts at the interfaces. Nevertheless, in our structures with intentionally deteriorated interfaces, we observed a significant full spin valve effect. A shift of the superconducting transition temperature Tc by switching the mutual orientation of the magnetizations of the two ferromagnetic Co layers from antiparallel to parallel amounted to ΔTc = 0.2 K at the optimal thickness of the superconducting Pb layer. Our findings verify the so far unconfirmed earlier results by Deutscher and Meunier on an F1/S/F2 heterostructure with oxidized interlayers [Deutscher, G.; Meunier, F. Phys. Rev. Lett. 1969, 22, 395. https://doi.org/10.1103/PhysRevLett.22.395] and suggest an alternative route to optimize the performance of superconducting spin valves.
Keywords: ferromagnet; insulator layers; proximity effect; superconducting spin-valve; superconductor